Smile Back at Me, But Only Once: Social Norms of Appropriate Nonverbal Intensity and Reciprocity Apply to Emoji Use. - Stein, Jan-Philipp (Journal of Nonverbal Behavior, 2023)
In computer-mediated communication, small graphical icons (emojis) can be used to compensate for the lack of nonverbal cues such as facial expressions or hand gestures. Accordingly, literature suggests that the use of emojis may also be subject to social norms—similar to nonverbal behavior in face-to-face interactions. However, actual empirical investigations into this assumption remain lacking. To remedy this research gap, I explored whether traditional norms of appropriate emotional intensity and reciprocity also apply to emoji usage. A first online experiment (N = 188) revealed that excessive emoji use in a first-contact scenario leads to diminished interpersonal outcomes, corresponding to the drawbacks of overly intense nonverbal displays in natural interactions. Proceeding to a different communicative stage, Experiment 2 (N = 242) explored nonverbal reciprocity with acquainted interaction partners. Inviting participants to reply to fictitious text messages (at varying levels of interpersonal intimacy), it was observed that stimulus messages containing more emojis also evoke stronger emoji use in return—indicating that principles of nonverbal attunement are in full effect during text-based online interactions.